Analysis of the internal temperature of the cells in a battery pack during SOC balancing - Mizanur, Rahman; Rashid, Muhammad Mahbubur; Rahman, Mohammed Ataur; Alam, A. H. M. Zahirul; Ihsan, Sany Izan; Mollik, M S (IOP Publishing, 2017)
ithium-ion batteries are more suitable for the application of electric vehicle due to high energy and power density compared to other rechargeable batteries. However, the battery pack temperature has a great impact on the overall performance, cycle life, normal charging- discharging behaviour and even safety. During rapid charge transferring process, the internal temperature may exceed its allowable limit (460C). In this paper, an analysis of internal temperature during charge balancing and discharging conditions is presented. Specific interest is paid to the effects of temperature on the different rate of ambient temperature and discharging current. Matlab/Simulink Li-ion battery model and quasi-resonant converter base balancing system are used to study the temperature effect. Rising internal temperature depends on the rate of balancing current and ambient temperature found in the simulation results.